System Perkawinan Matrilineal Di Suku Fehan Kabupaten Malaka - Maria contasya ingraini atitus; Noviani Vieaney; Stefanus Don Rade (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Marriage according to article 1 of law number 1 of 1974 concerning marriage. What is meant by marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on BELIEF IN THE ALMIGHTY GOD.This matrilineal marriage itself is known as "in-marriage" where if a couple has a child, then the lineage follows someone's descendants. Mother. The stages of the traditional Fehan wedding process in NTT will be explained below. Maybe this is a possibility, as happened at the traditional wedding ceremony in Malacca Regency.Matrilineal Marriage Process in Malaka Regency Engagement is the stage before the marriage is legal, where the prospective husband submits an application to the prospective wife's family and after reaching an agreement, both agree to carry out the marriage. A recent marriage binds the relationship between two people.The objects of collateral for a marriage or matrilineal marriage are goods that are sent from the male's extended family to the female's extended family in the form of betel nut and vice versa.It can be concluded that Malacca district in East Nusa Tenggara adheres to a matrilineal marriage system or often called incoming marriage, so in this matrilineal marriage system the man will leave and stay in the woman's house.